MSP AND IRRIGATION: KEY FACTORS FOR AGRICULTURAL DEVELOPMENT IN INDIA - Sharma, Suneyana; Kumar, Ashwani; Khosla, Pranav (ShodhKosh: Journal of Visual and Performing Arts, 2024)
Agricultural productivity is pivotal to India's economic development, necessitating a thorough investigation into its interplay with the Minimum Support Price (MSP) policy and irrigation infrastructure. This research focuses on three primary objectives: assessing the impact of MSP on agricultural productivity, exploring the relationship between irrigation facilities and productivity, and analyzing how MSP influences agricultural output. The findings indicate that MSP increases have been positively linked to higher wheat and paddy production, spurring both cultivation expansion and the modernization of farming practices to meet market demand and ensure food security. The MSP policy stands out as a key economic incentive, offering farmers income stability and boosting productivity when paired with effective irrigation systems.